Assessment of the Relationship between Entrepreneurial Skills and Intentions – The Case of Vietnam (International Journal of Scientific Research and Management (IJSRM), 2020)
At present, the nation start-up is considered as a national policy to innovate, exploit the intellectual, technological and new business models ... thereby creating more enterprise efficiency in many key industries, promoting the overall development of the economy. To become an entrepreneur, need to understand the start-up, the start-up process and most importantly, the skills you need to get started. Therefore, this article aims are to provide an overview of the start-up process and the relationship between different business skills, as well as how they relate to the students’ intentions. A questionnaire survey was conducted among 92 students who had to study/graduated in Business Administration. The survey asked participants to rate themselves based on their creativity, ambiguity, marshaling, finance and self-efficacy skills. The results can help universities develop curricula that combine teaching skills to equip both the knowledge and skills needed for students or those who want to be successfully entrepreneurs.